2009
DOI: 10.1677/erc-08-0152
|View full text |Cite
|
Sign up to set email alerts
|

Secretive and proliferative tumor profile helps to select the best imaging technique to identify postoperative persistent or relapsing medullary thyroid cancer

Abstract: In patients with postoperative persistent medullary thyroid cancer (MTC), the tumor detection rate is generally low for most of the imaging techniques now available. The aim of this study was to investigate if the clinico-biological profile of the tumor may indicate which imaging technique to perform in order to identify postoperative persistent or relapsing MTC foci. Thirty-five consecutive MTC patients with detectable and progressively increasing postoperative serum concentrations of calcitonin were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…O25 and O50 cells/mm 2 , can predict the presence of distant metastases and the risk of cancerrelated death with a sensitivity of 100% in both cases, and a specificity of 81 and 93% respectively. These data are fully consistent with those reported by Faggiano et al (22) who demonstrated that the MTC proliferative profile is a useful tool for selecting appropriate imaging techniques for persistent MTC patients: in particular, high Ki-67 scores earmarked patients expected to have positive FDG-PET results. In other words, high Ki-67 cutoffs could identify a subset of sporadic MTC cases with an aggressive behavior.…”
Section: Discussionsupporting
confidence: 91%
“…O25 and O50 cells/mm 2 , can predict the presence of distant metastases and the risk of cancerrelated death with a sensitivity of 100% in both cases, and a specificity of 81 and 93% respectively. These data are fully consistent with those reported by Faggiano et al (22) who demonstrated that the MTC proliferative profile is a useful tool for selecting appropriate imaging techniques for persistent MTC patients: in particular, high Ki-67 scores earmarked patients expected to have positive FDG-PET results. In other words, high Ki-67 cutoffs could identify a subset of sporadic MTC cases with an aggressive behavior.…”
Section: Discussionsupporting
confidence: 91%
“…Neuroendocrine tumours usually show an indolent course, and consequently low 18 F-FDG uptake. These tumours, however, when undergoing dedifferentiation become more aggressive and may show increased 18 F-FDG uptake, and this is also the case in MTC as demonstrated by the immunoreactivity for Ki-67 expression in surgically removed lesions [21,22]. When analysing 18 F-FDG PET results on the basis of CTDT, this tracer performs better in patients with higher calcitonin levels (>1,000 pg/ml) and/or with CTDT ≤12 months, again confirming that 18 F-FDG avidity is strictly related to the aggressiveness of the tumour [12,23].…”
Section: Discussionmentioning
confidence: 89%
“…Postoperative unsuppressed calcitonin and CEA concentrations may persist elevated during 2-3 months after surgery due to their long half-life in the blood, while increasing calcitonin and CEA serum levels after this time indicate disease persistence and progression (Leboulleux et al, 2004;Pacini et al, 2010;Faggiano et al, 2009). Undetectable basal serum calcitonin levels, further confirmed after a pentagastrin stimulation test, are a strong predictor of complete remission (Pacini et al, 2010).…”
Section: Diagnosis Of Mtc Persistence/relapse After Surgerymentioning
confidence: 99%
“…The evaluation of the clinico-biological and immunohistochemical tumor profile may be used in order to select the best imagine technique to be performed in patients with postoperative persistent or relapsing MTC. In particular, FDG-PET seems to correlate to tumor proliferation index Ki-67% and to be able to detect metastases in patients with postoperative persistent MTC when conventional imaging techniques are negative (Faggiano et al, 2009) (Figure 4). For advanced MTC, conventional oncological therapies (radiotherapy and systemic chemotherapy) have scarce effectiveness.…”
Section: Diagnosis Of Mtc Persistence/relapse After Surgerymentioning
confidence: 99%